Relaxation dynamics of magnetization transitions in synthetic antiferromagnet with perpendicular anisotropy. (8th March 2018) - Talantsev, A; Lu, Y; Fache, T; Lavanant, M; Hamadeh, A; Aristov, A; Koplak, O; Morgunov, R; Mangin, S
Abstract: Two synthetic antiferromagnet bilayer systems with strong perpendicular anisotropy CoFeB/Ta/CoFeB and Pt/Co/Ir/Co/Pt have been grown using sputtering techniques. For both systems two types of magnetization transitions have been studied. The first one concerns transitions from a state where magnetizations of the two magnetic layers are parallel ( P state) to a state where magnetizations of the two layers are aligned antiparallel ( AP state). The second one concerns transitions between the two possible antiparallel alignments ( AP +  to AP −). For both systems and both transitions after-effect measurements can be understood in the frame of nucleation—propagation model. Time derivative analysis of magnetic relaxation curves and mapping of the first order reversal curves at different temperature allowed us to demonstrate the presence of different pinning centers, which number can be controlled by magnetic field and temperature.